2022
DOI: 10.3390/biomedicines10123100
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Estrogen Receptor-Beta (ERβ) with PPZ0506 Antibody in Murine Tissue: From Pitfalls to Optimization

Abstract: The estrogen receptor beta (ERβ) is physiologically essential for reproductive biology and is implicated in various diseases. However, despite more than 20 years of intensive research on ERβ, there are still uncertainties about its distribution in tissues and cellular expression. Several studies show contrasts between mRNA and protein levels, and the use of knockout strategies revealed that many commercially available antibodies gave false-positive expression results. Recently, a specific monoclonal antibody a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…ERβ is known to be expressed in granulosa cells, but its expression in other cells including theca cells has been debated [ 19 ]. We performed immunohistochemistry (IHC) with an ERβ antibody (PPZ0506) that has been thoroughly validated across different tissues in humans and rodents [ 17 , 19 21 ]. We confirmed that ERβ was strongly expressed in the nucleus of granulosa cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ERβ is known to be expressed in granulosa cells, but its expression in other cells including theca cells has been debated [ 19 ]. We performed immunohistochemistry (IHC) with an ERβ antibody (PPZ0506) that has been thoroughly validated across different tissues in humans and rodents [ 17 , 19 21 ]. We confirmed that ERβ was strongly expressed in the nucleus of granulosa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mice lacking ERα are also infertile and develop cystic follicles [ 15 , 16 ]. ERβ, which is a homolog of ERα, has a noticeably more restricted expression pattern and is predominantly expressed in the granulosa cells of the ovary [ 17 21 ]. Its function is also less understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their expression differs between functional compartments of the ovary. While estrogen receptor beta (ERb, Esr2) is strongly expressed by granulosa cells in growing follicles (4)(5)(6)(7), estrogen receptor alpha (ERa, Esr1) is more diffusely expressed in interstitial and thecal cells (6)(7)(8). It is therefore not surprising that misregulation or depletion of these receptors has severe effects on physiological processes and impairs fertility (9).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of ERβ isoforms may diverge given differences in their three-dimensional structures and abilities to bind to ligands and other molecules. In addition, the function of ERβ may differ among humans, mice, and rats because different lengths and ligand binging affinities have been observed for these orthologs ( Petersen et al, 1998 ; O’Brien et al, 1999 ; Iwamoto et al, 2003 ; Donoghue et al, 2017 ; Schröder et al, 2022 ) ( Figure 1 ). The full-length wild-type ERβ1 isoform is typically referred to as ERβ, unless otherwise stated.…”
Section: Introductionmentioning
confidence: 99%